Formulation Development and Evaluation of Biodegradable Stent of Atorvastatin and Clopidogrel for Treatment of Atherosclerosis (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study aimed to create, develop, and optimize a biodegradable stent made of poly lactic co glycolic acid (PLGA) that contained clopidogrel and atorvastatin for the management of asthma. Solvent casting was used to create biodegradable stents. In particular, PLGA 75:25 polymer films were used to create stents using the solution-casting method. The base material was created by dissolving the polymer in isopropyl alcohol and adding PEG 400 as a plasticizer. As the active pharmaceutical ingredients in the stents, clopidogrel and atorvastatin were used. To avoid air bubbles, the resulting mixture was homogenized before being poured onto metal pans and allowed to gently evaporate in a refrigerator. The polymer films were then cut into strips, wound around cylindrical rods to form helical stents, and baked in an oven to guarantee that all of the isopropyl alcohol had evaporated. The biodegradable polylactic acid stents that included clopidogrel and atorvastatin demonstrated an impressive 99.34±0.44% encapsulation efficiency. Differential scanning calorimetry (DSC) analysis revealed that there were no chemical interactions between the stent's component parts. Significant water absorption over 80% was seen over a period of 8 days, which is remarkable. A thorough effect on disrupting plaque was seen at day 21, and on day 22, the stent began to biodegrade. Over the course of 20 days, the cumulative medication release percentage rose to 99.92%. According to the study's findings, treating atherosclerosis with an optimized biodegradable polymeric stent made of PLGA and combining atorvastatin and clopidogrel is a novel and promising treatment option.